Istirātījiyyah Murshidī al-Dīn fī Manʿ al-Zawāj al-Mubakkir bi Sabab al-Ḥaml Khārij Iṭār al-Zawāj fī Jākartā al-Sharqiyyah - Aziz, Abdul (Al-Zahra : Journal for Islamic and Arabic Studies, 2024)
Early marriage due to premarital pregnancy is a pressing social issue in East Jakarta, negatively impacting the health and well-being of children and families. This study aims to explore the strategies employed by religious counselors to prevent this phenomenon. Utilizing a qualitative approach, in-depth interviews were conducted with 7 religious counselors, with thematic analysis used to identify the strategies and challenges encountered. The findings indicate that religious counselors implement educational strategies through school outreach, parenting training, and social media campaigns targeting adolescents. They also collaborate with community organizations to reinforce prevention messages. However, challenges include a lack of community support, social stigma surrounding discussions of reproductive health, and limited resources for counseling programs. In conclusion, while the strategies employed by religious counselors are effective in raising awareness about the impacts of early marriage, stronger collaboration between the government, educational institutions, and the community is still needed to address this issue comprehensively. This study recommends strengthening outreach programs and increasing community engagement in the prevention of early marriage, in order to create a more conducive environment for the health and well-being of the younger generation.